Surgery for cholangiocarcinoma - Oliverius, Martin; Havlůj, Lukáš; Hajer, Jan; Soumarová, Renata; Hrudka, Jan; Gürlich, Robert (Casopis lekaru ceskych, 2019)
Cholangiocarcinoma represents the second most common primary liver malignancy. Despite it comprises only 3 % of all gastrointestinal malignancies, its incidence has been increasing recently. Cholangiocarcinomas are hepatobiliary cancers with features of cholangiocyte differentiation and from clinical point of view they are classified anatomically as intrahepatic or extrahepatic form. The only curative treatment with aim of long term and disease-free survival is surgery - liver resection or liver transplantation. Current progress in perioperative treatment and increased surgical skills has changed old treatment algorithms and widen number of patients suitable for curative treatment. On the other hand, surgical intervention is connected with not negligible morbidity and mortality. A rigorous knowledge of the disease extent and all prognostic factors is main condition for proper treatment decision.
Keywords: liver transplantation; dospělí; Hepatectomy; žlučové cesty intrahepatální; cholangiokarcinom; lidé; Liver Neoplasms; nádory jater; Klatskin tumor; Cholangiocarcinoma; hepatektomie; liver resection; cholangiocarcinoma; Adult; Bile Ducts, Intrahepatic; Humans